Ruloniniai mikrofilmai informaciniame darbe - Urbonas, Viktoras (Knygotyra, 1976)
Various information – search systems are described in the article, namely, “Rapid Selector”, “File Search”, “MIRACODE”, “RADIR”, “CRIS”, “Search-OK”, “Search–OK–1”, “Search DV–1”, “Search-Quint”, “Microfilm Selector of a medium capacity”, “Microfilm Selector of a large capacity OPI-104”, “Search-5”, “FLIP”, “Rapid Access Look – up System” and the microfilm selector under the sign of “International Business Machines Corp.” (USA), which uses not an optical way for plooting search images of documents on a microfilm but marks them on a magnetic tape.The author comes to the conclusion that information – search systems of this kind are less promissing for libraries then those which are based on a microfiche.